Enhancement of organic acids production from model kitchen waste via anaerobic digestion - Hafid, Halimatun Saadiah; Abdul Rahman, Nor'aini; Abd. Aziz, Suraini; Hassan, Mohd Ali (Academic Journals, 2011)
The aim of this study was to obtain the optimal conditions for organic acids production from anaerobic digestion of kitchen waste using response surface methodology (RSM). Fermentation was carried out using 250 ml shake flask which was incubated using an orbital shaker set at 200 rpm. Fermented kitchen wastes were used as inoculums sources. The individual and interactive effects of pH, temperature and inoculum size (%) on organic acids production from kitchen waste were investigated. The highest level of organic acid produced was 77 g/L at optimum pH, temperature, inoculum size of 6.02, 35.37°C and 20% inoculum, respectively. The results indicate that the most significant parameters affecting the bioconversion of kitchen waste to organic acids were temperature and inoculum size. Verification experiment of the estimated optimal conditions confirmed that RSM was useful for optimizing organic acids production from fermented kitchen waste.